(untitled) (Superficies y Vacío, 2014)
This work presents three MEMS mass sensor devices based in oscillating polysilicon cantilevers whose oscillation frequency shifts, due to corresponding changes of an added mass in the reaction container/area, can be better measured. An electrostatic actuator is used which consists of interdigitated electrodes configured to maximize the cantilever’s oscillation amplitude. In consequence, integration design issues between the microelectromechanical device and the signal conditioning and acquisition circuitry are addressed. These designs are to be fabricated in the SUMMiT-V process and they can be suitable for biological or chemical applications. The feasibility of the proposed designs is supported by a mathematical model and FEA calculations performed in COMSOL and ANSYS and mass resolutions of de 3.43 pg/Hz, 6.71 pg/Hz y 17.31 pg/Hz were obtained.